Shaw family papers - Felt, Joseph B. (Joseph Barlow), 1789-1869.; Osgood, Joseph B. F. (Joseph Barlow Felt), 1823-; New England Historic Genealogical Society
Correspondence, writings, copybooks, genealogical materials, reports, and other papers relating to the Shaw, Smith, Adams, and Felt (Felts) families. Central to the collection is the correspondence (1784-1818) of Abigail Adams with her sister, Elizabeth Smith Shaw Peabody, and with Elizabeth Peabody's children, Abigail Adams Shaw Felt and William Smith Shaw. Also includes correspondence of Elizabeth Peabody with her sister, Mary Smith Cranch; sermons and other papers (1822-1832) of Joseph B. Felt relating to New England; papers (1817-1892) of Felt's nephew, Joseph B.F. Osgood; material on state laws and practices regulating religious fasts and feasts, especially Thanksgiving; papers pertaining to ecclesiastical history including theological trends such as antinomianism and Arminianism; records (1849-1852) of the New England Historic Genealogical Society; court records (1731-1733) of the case of Woburn, Mass. vs. Rev. John Fox; Salem town records (1636-1820); and a review of manuscripts (1622-1782) concerning American colonies in the London State Paper Office.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Families represented include the Shaw, Smith, Adams, and Felt (Felts) families. Members represented include Abigail (Smith) Adams (Mrs. John Adams); her sister Elizabeth Smith Shaw Peabody; Elizabeth Peabody's children, Abigail Adams Shaw Felt and William Smith Shaw, secretary to John Adams; Rev. Joseph B. Felt, antiquarian and husband of Abigail Adams Shaw; and his nephew Joseph B.F. Osgood.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Genealogical guide to names represented in the Shaw family papers is available for use in the Manuscript Division Reading Room and at
Keywords: Adams, Abigail, -- 1744-1818 -- Correspondence; Cranch, Mary Smith, -- 1741-1811 -- Correspondence; Felt, Abigail Adams Shaw, -- 1790-1859 -- Correspondence; Fox, John, -- 1805-1884 -- Trials, litigation, etc; Peabody, Elizabeth Smith Shaw, -- 1750-1815 -- Correspondence; Shaw, William Smith, -- 1778-1826 -- Correspondence; Adams family; Felts family; Shaw family; Smith family; Woburn (Mass.) -- Trials, litigation, etc; Antinomianism; Arminianism; Cities and towns -- Massachusetts; Courts -- Massachusetts; Fasts and feasts; Genealogy -- Societies, etc; Religion; Thanksgiving Day; Theology; New England -- Social life and customs; Salem (Mass.) -- History; United States -- History -- Colonial period, ca. 1600-1775.; Authors; Secretaries